2003
DOI: 10.1191/0267659103pf687oa
|View full text |Cite
|
Sign up to set email alerts
|

Management of potential gas embolus during closure of an atrial septal defect in a three-year-old

Abstract: Gas embolism occurring in adult patients supported with cardiopulmonary bypass is usually associated with mechanical complications. Management of gas embolism is less often described for the pediatric or neonatal patient. Measures to counteract gas embolism must be undertaken immediately if a satisfactory outcome is to be achieved. Here, the management of a three-year-old female patient, who was undergoing repair of a secundum atrial septal defect when the aortic cannula became dislodged and air entered the ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Other sources of venous gas can occur such as air entrainment from vascular cannulation or operative sites. 2 In Case 1, gas most likely entered the venous circulation from the bronchial venous system, as well as mediastinal and intercostal veins that were disrupted as a result of the pulmonary barotrauma. The second case we describe manifested venous gas emboli without such a clear association with ventilation-related trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Other sources of venous gas can occur such as air entrainment from vascular cannulation or operative sites. 2 In Case 1, gas most likely entered the venous circulation from the bronchial venous system, as well as mediastinal and intercostal veins that were disrupted as a result of the pulmonary barotrauma. The second case we describe manifested venous gas emboli without such a clear association with ventilation-related trauma.…”
Section: Discussionmentioning
confidence: 99%
“…1,22 Although its use is not standardized, case reports have suggested administering RCP for 1 to 2 minutes at 28°C and with a pressure ranging from 20 to 40 mm Hg in the arterial line of the CPB circuit. [22][23][24][25] Other authors have reported that RCP should be administered for 5 minutes with a flow of 300 to 500 mL/min while maintaining jugular venous pressure <25 mm Hg. 26 In our case, it was decided to titrate flow according to pressure in the arterial line in order to maintain pressure between 40 and 45 mm Hg and avoiding any increase above this range to prevent cerebral edema.…”
Section: Restore the Oxygen Supply-demand Balancementioning
confidence: 99%
“…In the case of gross air embolism, these efforts have been highly successful, but occasional case reports continue to appear. 4 However, elimination of GME from conventional CPB has proved more difficult.…”
Section: Introductionmentioning
confidence: 99%